PENERAPAN MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) UNTUK PENCAPAIAN KEMAMPUAN KONEKSI MATEMATIK SISWA KELAS VII SMP NEGERI - Abdul Rosyid (Program Studi Pendidikan Matematika STKIP Muhammadiyah Kuningan, 2017)
The most of junior high students who do not understand the relevance of mathematical material make them often forget the material that has been studied. Junior high school students are still struggling in solving problems related to writing daily life problems into the form of mathematical models and difficulty in connecting between objects and concepts in mathematics. The difficulties of students in learning mathematics are elements of mathematical connection ability. It shows the ability of mathematical connections of students of class VII D SMP Negeri 46 Bandung which is still not optimal. Therefore, researchers apply the MMP (Missouri Mathematics Project) learning model to attempt to meet the achievement of students' mathematical connection ability. Achievement of students' mathematical connection ability is seen from the fulfillment of classical learning completeness criteria of 75.00% with KKM of 68 applicable in the class. The research method used is classroom action research method (PTK) which consists of three cycles. The instrument used in this research is a test instrument to measure the achievement of students' mathematical connection ability and attitude scale instrument to know the student's response to the learning of mathematics using MMP learning model. The result of this research is mathematical connection ability of students in every cycle and after all cycle have been reached and pertained good criterion. Achievement in the first cycle is 77.50%; in the second cycle is 82.05%; in the third cycle is 97.77%; and after the whole cycle is 94.44%.